2013
DOI: 10.1126/scisignal.2003220
|View full text |Cite
|
Sign up to set email alerts
|

Monovalent and Multivalent Ligation of the B Cell Receptor Exhibit Differential Dependence upon Syk and Src Family Kinases

Abstract: The Src and Syk families of kinases are two distinct sets of kinases that play critical roles in initiating membrane-proximal B cell receptor (BCR) signaling. However, unlike in other lymphocytes, such as T cells, the “division of labor” between Src family kinases (SFKs) and Syk in B cells is not well separated, because both Syk and SFKs can phosphorylate immunoreceptor tyrosine-based activation motifs (ITAMs) present in proteins comprising the B cell receptor (BCR). To understand why B cells require both SFKs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 67 publications
7
90
0
Order By: Relevance
“…1D). Unexpectedly, we found that SHIP-EGFP is significantly recruited to the plasma membrane when the BCR is ligated alone, and there is in fact no measurable difference in the magnitude of recruitment induced by F(ab9) 2 or intact anti-IgM (Fig. 1E).…”
Section: Fcgriib Engagement Does Not Significantly Impact Recruitmentmentioning
confidence: 76%
See 4 more Smart Citations
“…1D). Unexpectedly, we found that SHIP-EGFP is significantly recruited to the plasma membrane when the BCR is ligated alone, and there is in fact no measurable difference in the magnitude of recruitment induced by F(ab9) 2 or intact anti-IgM (Fig. 1E).…”
Section: Fcgriib Engagement Does Not Significantly Impact Recruitmentmentioning
confidence: 76%
“…Each group . Two-way ANOVA did not reveal any significant difference between F(ab9) 2 and intact anti-Ig. of recovery curves was then fit to the following equation, with the constraint that…”
Section: Frap Experimentsmentioning
confidence: 99%
See 3 more Smart Citations